Texts we wear - Tuz Daryna (My University, 2023)
The relevance of the research lies in the growing number of printed clothes that are becoming popular in the society. In fact, many famous brands use different texts for decorating their clothes which then perform a communicative function and create a general impression about a person. It gives rise to the required profound research of the texts we wear as a linguistic phenomenon. The object of the research is the texts found on different items of clothes, such as T-shirts, sweaters, dresses etc. The subject of the research is the semantic and structural characteristics of texts on clothes.
Keywords: texts on clothes